Guanidinoacetate Methyltransferase Deficiency: A Review of Guanidinoacetate Neurotoxicity - Marques,Eduardo P. (2016)
Abstract Guanidinoacetate methyltransferase (GAMT) deficiency is an autosomal recessively inherited disorder of the metabolism of creatine that leads to depleted levels of creatine and excessive concentrations of guanidinoacetate (GAA). Patients affected develop neurological symptoms during childhood, such as muscular hypotonia, involuntary extrapyramidal movements, convulsions, slurred speech, and even autism. Although the pathophysiology of GAMT deficiency is unclear, neurological dysfunction is commonly found in this disease, and it has been mainly attributed to a reduction in creatine or/and an increase in GAA levels. Reports from literature suggest that GAA may interfere with neuronal γ-aminobutyric acid (GABA) receptors type A and cause epilepsy in human. Preclinical studies show that GAA increases free radical formation and decreases brain antioxidant defenses, inducing alteration in oxidative status. Guanidinoacetate also impairs energy metabolism in brain. The discussion of this review focuses on various and latest studies addressing GAMT deficiency and creatine metabolism, as well as addresses the question of neurotoxicity GAA.